Relational Governance Mechanisms and Uncertainties in Nonownership Services. Issue 4 (April 2016) - Ndubisi, Nelson Oly; Ehret, Michael; Wirtz, Jochen
ABSTRACT: Entrepreneurs, managers, and consumers are attracted by the promise of nonownership services in the sharing economy—to enjoy benefits of assets without bearing the costs and downsides of ownership. Firms using nonownership contracts aim to transform uncertainties of clients (e.g., unpredictable changes in value of that asset, unforeseen costs such as repairs, or even black swan events) into business opportunities for providers. In many cases, the reality is that nonownership does not live up to the promised value propositions (as present in the struggle of companies such as Uber, BP, or the entire Biopharma industry) to exploit the potential of nonownership. This paper unveils the underlying paradox of nonownership, which aims at a smart allocation of uncertainty upsides and downsides between providers and clients. It identifies the potential of relational governance mechanisms to handle the uncertainty challenges apparent in nonownership. Further, it presents a pioneering case study of Rolls‐Royce airplane engines, which unveils the contribution of relational governance in unfolding the economic benefits of nonownership.